RIG-I-induced innate antiviral immunity protects mice from lethal SARS-CoV-2 infection - Samira Marx; Beate M. Kümmerer; Christian Grützner; Hiroki Kato; Martin Schlee; Marcel Renn; Eva Bartok; Gunther Hartmann (Elsevier, 2022)
The SARS-CoV-2 pandemic has underscored the need for rapidly usable prophylactic and antiviral treatments against emerging viruses. The targeted stimulation of antiviral innate immune receptors can trigger a broad antiviral response that also acts against new, unknown viruses. Here, we used the K18-hACE2 mouse model of COVID-19 to examine whether activation of the antiviral RNA receptor RIG-I protects mice from lethal SARS-CoV-2 infection and reduces disease severity. We found that prophylactic, systemic treatment of mice with the specific RIG-I ligand 3pRNA, but not type I interferon, 1-7 days before viral challenge, improved survival of mice by up to 50%. Survival was also improved with therapeutic 3pRNA treatment starting 1 day after viral challenge. This improved outcome was associated with lower viral load in oropharyngeal swabs and in the lungs and brains of 3pRNA-treated mice. Moreover, 3pRNA-treated mice exhibited reduced lung inflammation and developed a SARS-CoV-2-specific neutralizing antibody response. These results demonstrate that systemic RIG-I activation by therapeutic RNA oligonucleotide agonists is a promising strategy to convey effective, short-term antiviral protection against SARS-CoV-2 infection, and it has great potential as a broad-spectrum approach to constrain the spread of newly emerging viruses until virus-specific therapies and vaccines become available.